Enhanced Lysosomal Escape of pH-Responsive Polyethylenimine-Betaine Functionalized Carbon Nanotube for the Codelivery of Survivin Small Interfering RNA and Doxorubicin - Cao, Yue; Huang, Hao Yan; Chen, Li Qing; Du, Huan Huan; Cui, Jing Hao; Zhang, Leshuai W.; Lee, Beom Jin; Cao, Qing Ri (ACS Applied Materials and Interfaces, 2019)
The combination of gene therapy and chemotherapy has recently received considerable attention for cancer treatment. However, low transfection efficiency and poor endosomal escape of genes from nanocarriers strongly limit the success of the clinical use of small interfering RNA (siRNA). In this study, a novel pH-responsive, surface-modified single-walled carbon nanotube (SWCNT) was designed for the codelivery of doxorubicin (DOX) and survivin siRNA. Polyethylenimine (PEI) was covalently conjugated with betaine, and the resulting PEI-betaine (PB) was further synthesized with the oxidized SWCNT to form SWCNT-PB (SPB), which exhibits an excellent pH-responsive lysosomal escape of siRNA. SPB was modified with the targeting and penetrating peptide BR2 (SPBB), thereby achieving considerably higher uptake of siRNA than SWCNT-PEI (SP) or SPB. Furthermore, SPBB-siRNA presented substantially lower survivin expression and higher apoptotic index than Lipofectamine 2000. DOX and survivin siRNA were adsorbed onto SPB to form DOX-SPBB-siRNA, and siRNA/DOX was released into the cytoplasm and nuclei of adenocarcinomic human alveolar basal epithelial (A549) cells without lysosomal retention. Compared with SPBB-siRNA or DOX-SPBB treatment alone, DOX-SPBB-siRNA significantly reduced tumor volume in A549 cell-bearing nude mice, demonstrating the synergistic effects of DOX and survivin siRNA. Pathological analysis also indicated the potential therapeutic effects of DOX-SPBB-siRNA on tumors without distinct damages to normal tissues. In conclusion, the novel functionalized SWCNT loaded with DOX and survivin siRNA was successfully synthesized, and the nanocomplex exhibited effective antitumor effects both in vitro and in vivo, thereby providing an alternative strategy for the codelivery of antitumor drugs and genes.
Keywords: Functionalized carbon nanotubes; Pathological analysis; Singlewalled carbon nanotube (SWCNT); Small interfering RNA; Small interfering rna (siRNA); Survivin; SWCNT; Transfection efficiency; A549 Cells; Animals; Betaine; Doxorubicin; Drug Delivery Systems; Drug Resistance, Neoplasm; Genetic Therapy; Humans; Hydrogen-Ion Concentration; Lung Neoplasms; Lysosomes; Mice; Nanotubes, Carbon; Polyethyleneimine; RNA, Small Interfering; Survivin; Xenograft Model Antitumor Assays; betaines; BR2; DOX; PEI; survivin siRNA; SWCNT